A Rhetorical Study of Indonesian Football Supporters’ interaction on Social Media - Annisa Nurul Jannah; Eko Setyo Humaniika; Septi Riana Dewi (Universitas Sarjanawiyata Tamansiswa, 2026)
Social media has become a central space for football supporters to express support, criticism, and collective identity through diverse linguistic and rhetorical strategies. This study examines the linguistic characteristics, rhetorical elements, and gender-based rhetorical patterns in Indonesian football fans’ social media posts on Instagram and TikTok. Using a descriptive qualitative approach, data were collected through non-participant observation and analyzed through content analysis based on linguistic theory and Aristotle’s classical rhetoric, including stages of data reduction, tabulation, and conclusion drawing. The findings show that out of 60 analyzed posts, 24 display distinctive linguistic characteristics such as slang, figurative language, hashtags, and multimodality, while 29 posts employ rhetorical elements of ethos, pathos, and logos to convey support or criticism toward teams and players. In addition, 7 posts reveal gender-based differences in rhetorical patterns, with male supporters tending to use direct, evaluative, and analytical communication styles, whereas female supporters favor more emotionally expressive, supportive, and collaborative language. Overall, the study demonstrates that digital rhetoric within football supporter communities’ functions not only as a communication tool but also as a means of constructing collective identity, fostering emotional solidarity, and shaping persuasion in the digital public sphere.